PENGARUH INFUSA TEH HIJAU (CAMELLIA SINENSIS) TERHADAP DIAMETER NODULUS LIMFATIKUS LIMPA MENCIT (MUS MUSCULUS) YANG DIPAPAR ROKOK ELEKTRIK - Sidauruk, Dona Uli; Wahyuniari, Ida Ayu Ika; Linawati, Ni Made; Arijana, I Gusti Kamasan Nyoman (E-Jurnal Medika Udayana, 2024)
E-cigarettes are the most widely used nicotine replacement therapy (NRT), particularly among young people. Exposure to e-cigarette vapor increases free radicals and suppresses the body's immune system. The accumulation of reactive oxygen species (ROS) in the spleen causes inflammation and tissue injury that decreases immune reactivity. It causes changes in the histoarchitecture of the spleen, including the lymphatic nodules. It might be repaired by the antioxidant and immunomodulatory activity of green tea that stimulates and enhances the immune system. Green tea polyphenols affect the production of cytokines along with the activation, proliferation, and differentiation of lymphocytes in the body. Increasing the diameter of the lymphatic nodules is an indicator of the immunomodulatory activity of green tea in mice exposed to e-cigarette vapor. The study design was a randomized post-test only controlled group with 27 sampled mice divided randomly into 3 groups, namely; P0 (e-cigarette vapor), P1 (e-cigarette vapor + green tea 0.020 g/bb/day), and P2 (e-cigarette vapor + green tea 0.040 g/bb/day). There were significant differences between the control and treatment groups, while between green tea doses of 0.020 g/bb/day and 0.040 g/bb/day was no significant difference. The study showed green tea infusion with an optimal dose of 0.020g/bb/day affected increasing the diameter of the spleen lymphatic nodules of mice exposed to e-cigarette vapor. Further research based on the difference in duration of infusion exposure and overall observation of the white pulp component are needed. Keywords : Green tea infusion, Lymphatic nodules, E-cigarette vapor.